Unusual single crystal to single crystal phase transition of a nicotine salt monitored using temperature dependent single crystal X-ray diffraction. Issue 15 (24th March 2023) - Angevine, Devin J.; Mitchell, Travis; Zhang, Xiaotong; Benedict, Jason B.
Abstract : The organic salt ( S )-nicotinium 2, 6-dihydroxybenzoate undergoes reversible single crystal to single crystal phase transition at 104 K. Abstract : The organic salt ( S )-nicotinium 2, 6-dihydroxybenzoate undergoes reversible single crystal to single crystal phase transition at 104 K. The phase transition was monitored using temperature dependent single crystal X-ray diffraction and was attributed to symmetry breaking translations and rotations of the crystal components.